dbs Summer School Klinische Linguistik 2024. Sprachtherapie bei Kindern und Jugendlichen mit Schädel-Hirn-Trauma - Rosenkranz, A.; Kuhles, G.; Falkowska, Z.; Jaecks, P.; von Lehmden, F.; Büttner-Kunert, J.; Jonas, Kristina (Sprachtherapie aktuell: Forschung – Wissen – Transfer 13(1). dbs Summer School Klinische Linguistik)

Digitale Teilhabe in der Sprachtherapie: Perspektiven aus der Praxis Ergebnisse einer quantitativen Fragebogenerhebung - Thorndahl, Dennis; Rosenkranz, Anna; Jonas, Kristina (Logos)

Bridging the digital disability divide: supporting digital participation of individuals with speech, language, and communication disorders as a task for speech-language pathology - Thorndahl, Dennis; Abel, Miriam; Albrecht, Katharina; Rosenkranz, Anna; Jonas, Kristina (Frontiers in Communication)
Purpose The goal of speech-language pathology is to ensure and improve the participation of individuals with speech, language, and communication disorders. Continued digital transformation means more participation occurs through digital media, raising questions about the digital participation of these individuals and the role, content, and framework of speech-language pathology, both of which need proactive discussion. This Perspective Article outlines a viewpoint on these developments, aiming to stimulate critical reflection and disciplinary dialog on the future role of speech-language pathology in the digital age. Conclusion Research indicates that individuals with speech, language, and communication disorders are restricted in their digital participation. There is a lack of comprehensive understanding regarding the impact of various speech, language and communication skills on digital participation across different disorders. If speech-language pathology aims to promote participation and this is increasingly dependent on digital media and information and communication technologies (ICTs) then digital participation must also be a therapeutic goal. Achieving this requires more (participatory) research and corresponding training opportunities for speech language pathologists (SLPs).

Komplexe semantische Verarbeitung bei Kognitiven Kommunikationsstörungen: Vorstellung des ‚KomplexSem-Tests‘ - de Beer, Carola; Quinting, Jana; Fortmeier, Katharina; Hogrefe, Katharina; Hußmann, Katja; Jaecks, Petra; Jonas, Kristina; Richter, Kerstin; Rubi-Fessen, Ilona; Urbanczik, Gianna; Rosenkranz, Anna (Zeitschrift für Neuropsychologie)

Diagnostikmöglichkeiten von Kognitiven Kommunikationsstörungen – eine Umfrage unter praktisch tätigen Behandelnden - Rosenkranz, Anna; Thoma, Patrizia; Fortmeier, Katharina; Jonas, Kristina (Aphasie und verwandte Gebiete)

Unterrichtsintegrierte Diagnostik im Förderschwerpunkt Sprache – ein Überblick - Jonas, Kristina; Abel, Miriam Katharina (Sprachförderung und Sprachtherapie in Schule und Praxis)

The Co-CALIBRATE Framework: An Evidence-Based Framework for the Cultural Adaptation of Brain Injury Intervention Tools with Stakeholder Engagement. - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, B.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L.

Das Co-CALIBRATE Framework: Ein international konsentiertes, evidenzbasiertes Framework für kultur-sensitive Adaptationen von Therapie-Ressourcen im Bereich Sprach- und Kommunikationsstörungen nach Hirnschädigungen - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (Jahrestagung der Gesellschaft für Aphasieforschung und -behandlung (GAB) e.V., Aachen.)

Co-CALIBRATE: An Evidence-Based Framework For The Cultural Adaptation of Brain Injury Intervention Tools With Stakeholder Engagement - Quinting, J.; Avramovic, P.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (15. World Congress on Brain Injury, Montreal, Canada)

'Co-CALIBRATE: Developing a Culturally Sensitive Framework for Adapting ABI Interventions in Diverse Population - Avramovic, P.; Quinting, J.; Brassel, S.; Brunner, M.; Jonas, Kristina; Rietdijk, R.; Rubi-Fessen, I.; Stenneken, P.; Togher, L. (4th CCD Symposium, Coventry, UK.)

Entwicklung und Evaluation eines Förderkonzeptes der morphologischen Bewusstheit – Vorstellung eines Forschungsvorhabens [Poster] - Bodynek, Joanna; Gaigulo, Dana; Mayer, Andreas; Jonas, Kristina

Status quo of clinical use and scientific value of quality of life and neurocognitive assessment practice in neuro-oncological patients - Lucas, Carolin Weiss; Bumes, Elisabeth; Loução, Ricardo; Jonas, Kristina; Rosengarth, Katharina; Kochs, Sophia; Jost, Johanna; Wiewrodt, Dorothee; Lieker, Emma; Giordano, Frank A.; Golla, Heidrun; Renovanz, Mirjam; et al. (Brain and Spine)

Category naming for intraoperative monitoring of contextual association - Becker, Maura Luisa; Tampier, Carla; Keil, Phillip; Loução, Ricardo; Pieczweski, Julia; Timmer, Marco; Hampl, Jürgen; Kabbasch, Christoph; Jonas, Kristina; Goldbrunner, Roland; Lucas, Carolin Weiß (Brain and Spine)

Status quo of clinical use and scientific value of quality of life and neurocognitive assessment practice in neuro-oncological patients

Category naming for intraoperative monitoring of contextual association

Digital participation of brain tumour patients in the assessment and treatment of communication disorders - Weiss Lucas, C; Kochs, S; Jost, J; Loução, R; Kocher, M; Goldbrunner, R; Wiewrodt, D; Jonas, Kristina (Frontiers in. Psychology)

Editorial: Digital participation and communication disorders across the lifespan - Jonas, Kristina; Jaecks, P; Frieg, H (Frontiers in. Psychology)

Sonderpädagogische Diagnostik im Feststellungsprozess: Eine Ist-Stand-Analyse und der Blick nach vorn - Hennes, A.K.; Philippek, J.; Dortants, L.; Abel, Miriam Katharina; Baysel, K.; Dworschak, W.; Fabel, L.; Hövel, D.; Jonas, Kristina; Nideröst, M.; Rösli, P.; Schabmann, A.; et al. (Zeitschrift für Heilpädagogik)

Intraoperative Monitoring of Visuospatial and Linguistic Skills: Scenario Description for a More Standardised Practice - Tampier, Carla; Keil, Phillip; Becker, Maura; Jonas, Kristina; Goldbrunner, Roland; Lucas, Carolin Weiss (Brain and Spine)

Kurzfassung und interdisziplinäre Kommentierung der internationalen INCOG-2.0-Leitlinie „Kognitive Kommunikationsstörungen nach Schädelhirntrauma“ - Thoma, Patrizia; Quinting, Jana; Jonas, Kristina; Regenbrecht, Frank; Schumacher, Rahel; Büttner-Kunert, Julia (Zeitschrift für Neuropsychologie)
Zusammenfassung: Kognitive Kommunikationsstörungen (Cognitive Communication Disorders = CCDs) bezeichnen kommunikative Beeinträchtigungen, die v. a. die kommunikativ-pragmatischen Fähigkeiten betreffen und primär durch begleitende kognitive Störungen, z. B. der Gedächtnis-, Aufmerksamkeits-, und exekutiven Planungsfunktionen bedingt sind. Eine besondere Rolle spielen außerdem Beeinträchtigungen Sozialer Kognition (z. B. Empathie, Theory of Mind). Somit fällt die Diagnostik und Behandlung der CCDs interdisziplinär in den Zuständigkeitsbereich der Klinischen Neuropsychologie und der Sprachtherapie. Ein internationales, interdisziplinäres Netzwerk, die sog. INCOG-Arbeitsgruppe, hat im Jahre 2023 aktualisierte, evidenzbasierte Empfehlungen zur Diagnostik und Behandlung von CCDs und begleitender soziokognitiver Störungen spezifisch nach mittelschweren bis schweren Schädel-Hirn-Traumata veröffentlicht. Diese sollen im vorliegenden Artikel zusammenfassend vorgestellt und kommentiert werden. Es werden erste Vorschläge zur konkreten interdisziplinären Zusammenarbeit von Klinischer Neuropsychologie und Sprachtherapie abgeleitet.